PENGEMBANGAN SIK BERBASIS IOT DALAM PEMANTAUAN PASIEN KRONIS DI DAERAH TERPENCIL - Muhammad Fahri (LPPM Universitas Awal Bros, 2025)
This study discusses the implementation of Health Information System based on Internet of Things (IoT) to monitor patients with chronic conditions in remote areas. The main focus of this study is on the challenges faced in limited medical infrastructure and resources, which often hinder access and quality of health services in these areas. The main objective of this study is to examine how IoT can improve the effectiveness of remote and real-time chronic patient monitoring, and to identify factors that influence the success or obstacles in its implementation. The method used in this study is a systematic literature review, by analyzing 20 relevant scientific articles, covering technical, managerial, and social aspects of the application of IoT technology in the health sector. The results of the study indicate that although IoT offers great potential in improving patient health monitoring, the main challenges faced are limited communication infrastructure and a shortage of medical personnel trained in the use of this technology. These findings also highlight the importance of policies that support the development of digital infrastructure and continuous training for medical personnel in remote areas. Overall, this study makes a significant contribution to the development of IoT-based health systems, by providing an understanding of the challenges and opportunities in implementing technology in resource-limited areas, as well as providing practical recommendations for the development of more inclusive and sustainable health policies and technologies.